Item Analysis - Christopher Reznich (Association of American Medical Colleges, 2012)
Abstract This resource is an electronic tutorial explaining the basics of item analysis. It focuses on item difficulty, item discrimination, and distractor analysis. Illustrative examples are included in the tutorial, and brief exercises in reading an item analysis report are included in the User's Guide. The resource was developed in response to a voiced need by faculty at the College of Human Medicine, Michigan State University, for training in basic concepts of item analysis. An online version was created to meet ongoing faculty development needs for training in the topic. It should take approximately 30 minutes to complete. The resource has been successfully implemented within the College of Human Medicine with no reports of problems. Faculty comments indicate that it is easy to use and technologically reliable.